Anti-angiogenic therapy or immunotherapy? A real-world study of patients with advanced non-small cell lung cancer with EGFR/HER2 exon 20 insertion mutations - Li, Jiaqi; Xie, Mengqing; Zhao, Ruiying; Qiang, Huiping; Chang, Qing; Qian, Jialin; Lu, Haijiao; Shen, Yinchen; Han, Yuchen; Su, Chunxia; Chu, Tianqing (Frontiers in Oncology, 2024)
Background. For patients with EGFR/HER2 exon20 insertions, platinum-containing doubledrug chemotherapy is still the standard treatment method. First-generation TKIs have almost no therapeutic activity against EGFR exon 20 insertions. The efficacy of second-and thirdgeneration TKIs is still controversial. Immunotherapy research is scarce, and there is an urgent need for more evidence and new treatment options for this group of patients.Methods. We reviewed patients with advanced NSCLC with EGFR/HER2 exon 20 insertion mutations treated in Shanghai Chest Hospital and Shanghai Pulmonary Hospital from 2015 to 2022 and assessed the efficacy of receiving chemotherapy, anti-angiogenic therapy and immunotherapy, including objective response rate (ORR) and disease control rate (DCR), and compared progression-free survival (PFS) and overall survival (OS).Of the 126 patients included in the study, 51 patients had EGFR20ins mutations and 7 5 patients had HER2-20ins mutations. In the first-line treatment ， bevacizumab + chemotherapy (Beva+Chemo), ICI+chemotherapy (ICI+Chemo) , compared with chemotherapy alone (Chemo), ORR: 40% vs 33.3% vs 15% (p=0.0168 ); DCR: 84% vs 80.9% vs 67.5% (p=0.1817); median PFS: 8.3 vs 7.0 vs 4.6 months (p=0.0032), ICI+Chemo has a trend of benefiting on OS. Stratified analysis showed that compared with chemotherapy, ICI+Chemo was more effective for EGFR20ins mutation with median PFS: 10.3 vs. 6.3m (P=0.013); Beva+Chemo was more effective for HER2-20ins mutation, with a median PFS: 6.63 vs. 4.31m (p=0.030). In the second-line treatment of EGFR20ins mutation, bevacizumab + chemotherapy has a significant advantage in PFS compared with targeted therapy, median PFS:10.8 vs 4.0 months (P=0.016).For patients with EGFR20ins mutation, compared to chemotherapy, ICI+Chemo prolongs PFS, and after chemotherapy progression, bevacizumab combined with chemotherapy seems better than Furmonertinib-based targeted therapy on PFS. For HER2-20ins mutation, Beva+Chemo may be a better choice.